Improvement of tuned mass damper by using rotational inertia through tuned viscous mass damper - Garrido, Carlos Hernán (2013)
A new vibration control device called a rotational inertia double-tuned mass damper (RIDTMD) is proposed in this paper. The device consists of a tuned mass damper (TMD) in which the typical viscous damper is replaced with a tuned viscous mass damper. The linear model for a single-degree-of-freedom structure incorporating an RIDTMD, the equations of motion in state-space representations, and the transfer function of the considered model are derived. The optimum design parameters of the system subjected to harmonic load are obtained by using a numeric technique, and the performance of the new device is compared with that of a traditional TMD in terms of frequency response. The strokes of auxiliary masses are also assessed. Based on the results, it is demonstrated that the RIDTMD is more effective than a TMD at the same mass ratio, particularly at excitation frequencies near resonance. Moreover, the suppression band is wider and the moving block stroke is nearly identical for both devices.